Observation and interpretation of the 5p54f35d core-excited configuration in triply ionized neodymium Nd3+ (Nd IV). (May 2019) - Arab, Kamel; Deghiche, Djamel; Meftah, Ali; Wyart, Jean-François; Tchang-Brillet, Wan-Ü Lydia; Champion, Norbert; Blaess, Christophe; Lamrous, Omar
Highlights: Extended analysis of the triply ionized neodymium Nd IV vacuum UV spectrum. Determination of unknown energy levels belonging to a core-excited configuration. Assessement of effects of configuration interactions on transition probabilities. Abstract: Ultraviolet laboratory observation of the emission spectrum of the triply ionized neodymium Nd IV excited in a vacuum spark source was extended to shorter wavelength region down to 350 Å. The present analysis, based on the identification of 313 spectral lines, led to the determination of 125 previously unknown energy levels, all but two belonging to the core-excited configuration 5p 5 4f 3 5d in the Nd 3 + ion. Theoretical calculations of even parity configurations were performed by using the parametric Slater-Racah method including configuration interactions. Energy parameter values were fitted by least-squares with a root-mean-square (rms) deviation of 184 cm − 1 for an average energy E av (5p 5 4f 3 5d) = 221 076 cm − 1 . In this work, we quantitatively confirm the effect of reduction of the 5p 6 4f 3 - 5p 6 4f 2 5d transition probabilities by the configuration interaction between 5p 6 4f 2 5d and core-excited 5p 5 4f 3 5d configurations, which is similar to the one observed in Nd V for the 5p 6 4f 2 - 5p 6 4f5d transitions.